A General Layer‐by‐Layer Printing Method for Scalable High‐Resolution Full‐Color Flexible Luminescent Patterns. Issue 12 (22nd April 2019) - Zhao, Cong; Li, Huizeng; Wang, Yang; Li, Kaixuan; Hou, Jue; Ma, Ying; Li, Mingzhu; Song, Yanlin
Abstract: High‐resolution scalable and colorful flexible luminescent patterns are prepared through an alternate printing method in a layer‐by‐layer (LBL) manner without any patterned substrates or masks. The novel embedding self‐assembly process retains high resolution to the sub‐micrometer level. This method is applied to achieve high‐resolution red, green, and blue (RGB) pixel array patterns, standard white light patterns, and various cross‐typed patterns. The fabricating process is flexible and straightforward, making it useful for diverse applications in patterning nanocomposites for wearable optoelectronic devices. Abstract : A general layer‐by‐layer printing method is applied to achieve high‐resolution red, green and blue (RGB) pixel array patterns, standard white light patterns, and various cross‐typed patterns without any patterned substrates or masks. The novel embedded self‐assembly process retains high resolution to the sub‐micrometer level. The nanospheres are assembled into a highly ordered photonic crystal structure to improve the fluorescence intensity.